How to create your own gig posters, band T-shirts, album covers & stickers : screenprinting, photocopy art, mixed-media collage, and other guerilla poster styles /: screenprinting, photocopy art, mixed-media collage, and other guerilla poster styles. (2013) - Unknown
No abstract available